Species composition and chemical characterization of Sargassum influx at six different locations along the Mexican Caribbean coast - Vázquez-Delfín, Erika; Freile-Pelegrín, Yolanda; Salazar-Garibay, Adán; Serviere-Zaragoza, Elisa; Méndez-Rodríguez, Lia C.; Robledo, Daniel (The Science of the total environment, 2021)
In the last decade, unprecedented arrivals of pelagic Sargassum (Sargassum influx) have been reported for the Caribbean coasts causing severe ecological and economical affectations and remarking the necessity to characterize the phenomenon. In the north coast of the Mexican Caribbean, spatial characterization of Sargassum influx was performed in terms of its abundance, species composition and chemical content using a combination of in situ sampling and remote sensing evaluations. Sargassum influx was detected within the 25 km fringe near to Quintana Roo coast in coincidence with beach-cast events during September 2018. Significant spatial variation in abundance and species composition of the stranded biomass was found for the six localities studied, which was related to the local environmental conditions. Pelagic species of Sargassum were the main component ranging from 78.1 to 99.6% of the total beach-cast (wrack) fresh biomass, whereas benthic macrophytes (seagrasses and macroalgae) were a minor component reaching up to 21% in some localities. The biochemical composition of beach-cast Sargassum resulted spatially homogeneous for most of the components analyzed; only carbon tissue content, ash metals (particularly Fe and As) and isotopic composition changed spatially. This study represents baseline information for the region. Long-term seasonal evaluations of Sargassum influx along Mexican Caribbean are required to define adequate management strategies and exploitation. [Display omitted] •Floating Sargassum covered from 21,116 to 607,579 m2 in the Mexican Caribbean.•Beach-cast biomass ranged from 0 to 5.7 ± 2.6 kg dw m−2 depending on locality.•Species composition of the beach-cast biomass varied spatially.•Pelagic Sargassum ranged between 78.1 and 99.6% of the total fresh stranded biomass.•Chemical composition of Sargassum was spatially homogeneous for most components.